The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/macp.201800311
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the Graft Length and Graft Density of Irradiation‐Grafted Copolymers

Abstract: Graft CopolymersIrradiation-induced graft copolymerization is often the easiest route to combine the functionality of two polymers and, furthermore, the average composition of the copolymer is straightforward to control. However, control of the graft length and the graft density is more difficult and has been considered to be infeasible. To test the hypothesis that the graft density and graft length may be increased or decreased via increasing or decreasing the dose of irradiation and graft level, polymer elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The scattering intensity profiles, I ( q ), for representative f D 2 O are shown in Figure . In agreement with previously reported scattering profiles, three typical features in the scattering profiles of ETFE-g-PSSA PEMs can be observed in three specific regions. Thus, we defined the corresponding regions in the figure as follows: A small- q upturn in the low- q region at q < 0.12 nm –1 (region I), a broad shoulder-like scattering peak in the middle- q region at 0.12 < q < 1.5 nm –1 (region II), and a distinct scattering peak in the high- q region at q > 1.5 nm –1 (region III).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The scattering intensity profiles, I ( q ), for representative f D 2 O are shown in Figure . In agreement with previously reported scattering profiles, three typical features in the scattering profiles of ETFE-g-PSSA PEMs can be observed in three specific regions. Thus, we defined the corresponding regions in the figure as follows: A small- q upturn in the low- q region at q < 0.12 nm –1 (region I), a broad shoulder-like scattering peak in the middle- q region at 0.12 < q < 1.5 nm –1 (region II), and a distinct scattering peak in the high- q region at q > 1.5 nm –1 (region III).…”
Section: Resultssupporting
confidence: 91%
“…This difference might be the reason for the low swelling of the ETFE-g-PSSA PEM under fully hydrated conditions, whereas lower conductivity under the low relative humidity (RH) conditions as compared to Nafion . This new finding is remarkably more advanced than the traditional structural analysis based on the scattering intensity profile, which specifies only the information of ionomer peaks but not the accurate assignment of each component. This study demonstrates for the first time the repulsive behavior between GPs and water on a small length scale (molecular level) by the delicate PSF analysis using the contrast-variation SANS technique. This structural factor is believed to affect the membrane conductivity significantly and requires special attention for future PEM design.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was reported that the amorphous ETFE zones and PSSA chains in ETFE-PEM are immiscible. [53,60] Moreover, the higher-order microstructures of ETFE-PEM revealed by SAXS indicate that the PSSA chains were generated mainly inside the lamellae with a GD of 0%-34% and outside with a GD higher than 34%. [8,10,11] Thus, these different amorphous arrangements include the lamellar amorphous within the lamellae and mobile amorphous regions outside of the lamellar as well as the PSSA layers.…”
Section: Pals Results Of the Threecomponent Modelmentioning
confidence: 97%
“…All materials, reagents, and detailed procedures for the preparation of ETFE-PEMs are similar to those described previously. [7,9] Briefly, the ETFE films (50 μm) (Asahi Glass Co. Ltd., Japan) were irradiated using gamma rays from a 60 Co radioisotope source at a dose and dose rate of 15 kGy and 15 kGy/h, respectively. The graft polymerization was conducted by immersing the irradiated film in a styrene solution of toluene at 60 C. The grafting degree (GD) is determined by the following equation: GD (%) = 100(W g À W o )/W o , where W g and W o are the weights of the films after and before graft polymerization, respectively.…”
Section: Materials and Preparationmentioning
confidence: 99%